Nutrition abnormalities in mothers and children as a risk factor for disorders in communication skills development - Kaczorowska-Bray, Katarzyna (Papers in Linguistics, 2024)
Eating disorders are diagnosed in 8 to 10% of women, with their peak prevalence at the beginning of the reproductive age, i.e. at the end of adolescence. The available literature shows that children of such mothers show an increased risk of developmental disorders, including cognitive, social and emotional problems. Improper, unbalanced diet of both mothers and their offspring should also be considered a factor increasing the risk of developmental difficulties, including speech and language development disorders. Primary logopedic prevention should include activities aimed at shaping the right approach and spreading knowledge about the impact of a proper diet on reproductive capabilities, women’s health, the course of pregnancy and childbirth as well as child development in all its aspects